2017
DOI: 10.5539/jas.v9n7p58
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Root Traits of Spring and Winter Canola (Brassica napus L.) under Controlled and Water Stressed Conditions

Abstract: Root system in canola (Brassica napus L.) varies largely in different growth habit types. A study was conducted with five winter and five spring types of canola germplasm. The objective was to identify the gradual change of root traits at different growth habits stages under controlled and water stressed conditions. Two experiments, controlled and water stressed, were conducted in a greenhouse. Data on different root traits were collected at 30, 40, 50 and 60 days after planting. In controlled experiment, no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The winter-type (along with winter fodder and semi-winter) accessions were characterized by greater biomass production and larger root system size compared to the spring-type ones (Figure 2). Superior root features were already reported for these genotypes having a longer life cycle that necessitates vernalization (Rahman & McClean, 2013;Thomas et al, 2016a;Arifuzzaman & Rahman, 2017).…”
Section: Phenotyping Of the F2 Progenies And Block Regressionmentioning
confidence: 53%
“…The winter-type (along with winter fodder and semi-winter) accessions were characterized by greater biomass production and larger root system size compared to the spring-type ones (Figure 2). Superior root features were already reported for these genotypes having a longer life cycle that necessitates vernalization (Rahman & McClean, 2013;Thomas et al, 2016a;Arifuzzaman & Rahman, 2017).…”
Section: Phenotyping Of the F2 Progenies And Block Regressionmentioning
confidence: 53%
“…Root architectural traits can serve as a focal point for enhancement and optimization, tailored to meet the specific requirements dictated by soil conditions (Arifuzzaman and Rahman, 2017). For example, Thomas et al (2016) examined the root structure of various growth types of B. napus and determined that root morphology has the potential to enhance crop yield, provided that appropriate genetic markers associated with agronomic traits can be identified (Arifuzzaman and Rahman, 2017). The findings from this study revealed that root traits dynamics were significantly influenced by the genotype and species, highlighting the significant role of genetic factors in RSA.…”
Section: Discussionmentioning
confidence: 99%
“…Root architectural traits can serve as a focal point for enhancement and optimization, tailored to meet the specific requirements dictated by soil conditions ( Arifuzzaman and Rahman, 2017 ). For example, Thomas et al.…”
Section: Discussionmentioning
confidence: 99%